Organizational Transformation at the Government Procurement Bureau of Goods and Services in Banten Province - Dian Permata Puspita; Heru Nurasa; Ramadhan Pancasilawan (Jurnal Manajemen Pelayanan Publik, 2023)
This research is based on indications of problems including budget composition and limited authority for the Bureau of Procurement of Goods and Services, lack of apparatus human resources to support the implementation of programs and activities, and decreased performance after the implementation of organizational transformation. Moreover, this research purposes to explore the transformation. The theory used in this study is the theory of organizational transformation from Gouillart and Kelly (1995). The research method uses qualitative methods with the purposive determination of informants. The results of the study show that the reframing dimension has been carried out well through the actions of achieving mobilization, creating the vision, and building a measurement system. In the restructuring dimension, they have carried out the actions of constructing the organization model and aligning the physical infrastructure, but have not finished carrying out the actions of redesigning the work architecture. Meanwhile, in the revitalization dimension, efforts have been made to achieve market focus, trying to invent new businesses and implement changes to the rules through information technology. Finally, the renewal dimension has not carried out optimally the actions to create a reward structure, build individual learning, and develop the organization. In conclusion, organizational transformation has not run optimally due to several obstacles such as still using old SOPs, lack of facilities and infrastructure as well as unstructured and unsustainable education and training programs for employees.